Mutant Operators for Testing Concurrent Java Programs - Delamaro, Márcio; Pezzè, Mauro; Vincenzi, Auri M. R. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2001.23994, 2001)
Mutation testing is a fault-based testing technique that has been widely studied in the last decades. One reason for the interest of the scientific community in mutation testing is its flexibility. It can be applied to programs at unit and integration testing levels, as well as to software specifications written in a variety of different languages. A fundamental issue to make mutation testing work for a given language or environment is the set of mutant operators used to create the mutants. In this paper a set o mutant operator is proposed for the Java programming language, and more specifically, aiming at exercising aspects of concurrency and synchronization of that language.